The challenges of implementing the green building concept among construction industry players in the East Coast Region / Tanti Lyana Farisha Mohd Zulkarnain and Izatul Farrita Mohd Kamar - Mohd Zulkarnain, Tanti Lyana Farisha; Mohd Kamar, Izatul Farrita (2023)
The green building maximises resource efficiency, minimises environmental damage, and enhances human health. Despite the advantages, green building concepts must be implemented amid financial restrictions in Malaysia's construction industry. This research aimed to identify the challenges of implementing the green building concept among construction industry players in the East Coast Region. This research focuses on the East Coast Region because few green buildings are being constructed there, and greater awareness is needed from the general public and those involved in the construction of green buildings to make implementing this concept grow more rapidly. The research methodology used to gather the data is a structured interview conducted among the construction players involved in the green building project in the East Coast Region. The data gathered will be analysed using a qualitative data analysis tool, ATLAS.ti. The findings show several challenges to implementing the green building concept, such as financial constraints, a lack of awareness and a shortage of specialists. The findings may help achieve one of the 17 Sustainable Development Goals and the 12th Malaysia Plan.